2020
DOI: 10.3390/su12198169
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education for Sustainable Development on Romanian Economics and Business Students’ Behavior

Abstract: Education for sustainable development (ESD) has presented long-lasting interest for researchers and policy makers. Despite a significant body of research, more in depth empirical studies are required for a better understanding of how sustainable development goals are applied in higher education and how sustainable behavior could be shaped via ESD. The need for this kind of research arises from, first, the scarceness of existing studies that explore economic and business higher education, and, second, the neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 79 publications
0
25
0
4
Order By: Relevance
“…The relation between sustainability and quality teaching has been kept. All in all, the strategic plan is aligned to the university's interest in sustainability, which has also been indicated by the studies carried out and discussed in the literature review [63][64][65][66].…”
Section: Bucharest University Of Economic Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…The relation between sustainability and quality teaching has been kept. All in all, the strategic plan is aligned to the university's interest in sustainability, which has also been indicated by the studies carried out and discussed in the literature review [63][64][65][66].…”
Section: Bucharest University Of Economic Studiesmentioning
confidence: 94%
“…On the one hand, the students pursuing a degree at the Faculty of Business and Administration of the University of Bucharest have participated in a survey that has shown that "social responsibility activities contribute to the development of sustainable higher education institutions through the active engagement and participation of their students" [62] (p. 447). On the other hand, the students at the Bucharest University of Economic Studies have expressed their opinions on the way in which the "sustainable campus initiatives, teaching staff involvement and curricula" [63] (p. 1) have helped them to develop sustainable behaviors. The sustainability topics approached in class and teachers' involvement in raising students' "awareness of the sustainability issues are crucial to students' sustainable behavior" [63] (p. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the COVID-19 pandemic outbreak in 2020, an event that confined to their homes more than 1.37 billion students of all levels of education, according to the statistics provided by UNESCO [9], studies on students' environment-related behaviors dealt with either their behavior on campus [10], at college or as part of their generation, in the household, from multiple angles-as part of a lifestyle [11], as a consciously adopted choice [12], as perceptions related to sustainability actions in green universities [10], up to behaviors and attitudes on campus [13,14]. Universities also attracted their share of attention, mainly in the form of calls to action under the framework of the United Nations Environment Programme for going green and joining the Green Universities Network (UNEP) [15], or as practices developed on regional or local levels [10,[16][17][18]. The health crisis interrupted much of the habitual academic life and forced universities to focus on their capacity to deliver education and reduce the disruptive force of the pandemic on academic life, by accelerating the adoption of digitalization [19], a topic that was viewed mainly from a technological angle and with an impact on educational practice, but that has a spillover effect on the environmental concerns and greening, if the reduction of physical paper is taken under consideration.…”
Section: Introductionmentioning
confidence: 99%